Effectiveness of Neurodevelopmental Therapy on Trunk Control and Sitting Balance in Children with Spastic Quadriplegic Cerebral Palsy: A Quasi-Experimental Study - Dr. Rosaline Sujitha J; Dr. Kishoremoy Das; Dr. Vignesh Srinivasan; Dr. SenthilKumar N; Iswarya S (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Background: Spastic quadriplegic cerebral palsy (CP) severely limits trunk control and sitting balance. Neurodevelopmental therapy (NDT) is widely used, yet its added value over conventional physiotherapy remains debated. Methods: Thirty children (6–10 years; GMFCS III–IV) with spastic quadriplegic CP were allocated to NDT + conventional therapy (n = 15) or conventional therapy alone (n = 15) for 6 weeks, three 45-min sessions per week. Gross Motor Function Measure-88 (GMFM-88) and Trunk Control Measurement Scale (TCMS) were recorded pre- and post-intervention. Paired and unpaired t-tests compared within- and between-group change. Results: Both groups improved significantly. In the NDT arm GMFM rose from 30.22 ± 5.79 to 35.19 ± 5.81 (p < 0.001) and TCMS from 11.07 ± 1.90 to 15.34 ± 2.60 (p < 0.001). Conventional therapy produced smaller gains (GMFM 30.05 ± 4.97 → 31.47 ± 5.21, p = 0.0003; TCMS 11.18 ± 3.05 → 12.71 ± 2.97, p < 0.001). Between-group comparison showed a clinically relevant but non-significant difference for GMFM (p = 0.075) and a significant advantage for NDT on TCMS (p = 0.015). Conclusion: Adding NDT to conventional exercises yields greater improvements in trunk control and sitting balance than conventional therapy alone in children with spastic quadriplegic CP.